Analysis Benefit Costs, Number of Tourist Visits (Domestic & International) and Per Capita Income on Conservation Forest Management in Jambi Province - Safri, Muhammad (International Journal of Membrane Science and Technology, 2023)
This study aims to analyze the effect of benefit costs (X1), the number of visits by domestic tourists or foreign tourists (X2) and per capita income (X3) on the management of Jambi Province's conservation forest (Y). The data in this study were analyzed using Benefit Cost Ratio (BCR) analysis and multiple linear regression tests. Benefit cost analysis is carried out to calculate the amount of benefits and costs required from a project, if BCR ? 1 then the project is considered feasible and vice versa if BCR ? 1 is considered not feasible. And multiple linear regression analysis is used to determine the effect between variables. The results of the BCR calculations all get results ? 1, then there is an influence given by the variables X1, X2, X3 on variable Y. So it can be concluded that the project was declared not feasible.